Performance of a MEA using patterned membrane with a directly coated electrode by the bar-coating method in a direct methanol fuel cell. (14th June 2018) - Kang, Saetbyeol; Bae, Gyuna; Kim, Sang-Kyung; Jung, Doo-Hwan; Shul, Yong-Gun; Peck, Dong-Hyun
Abstract: This study increased the surface area of a membrane by forming patterns on the Nafion resin membrane using a stainless steel mesh to enhance the performance of a direct methanol fuel cell (DMFC) because the triple-phase boundary is extended. Nafion resin (F-form (SO3 F)) was used which has melt-moldability to form a stable surface pattern and to directly coat the catalyst layer by the bar-coating method. The performance (polarization and power density curves) and the resistance of the membrane-electrode assembly (MEA) were analyzed with a single cell and an impedance analyzer. The surface area of the patterned membranes was increased 1.99, 2.10, and 2.12 times compared to the flat membrane, and the power density also increased 12.9, 18.6, and 24.2% at 0.4 V, respectively. The performance of the MEA with the patterned membrane had a lower concentration polarization than that of the MEA with the flat membrane. The performance of the MEAs with the patterned membranes had a greater impact on the cathode side of the membrane than on the anode side. The results of these experiments offer a solution to the problem of a low performance of MEA, which is one of the disadvantages of DMFCs. Graphical abstract: Highlights: The catalyst layer was directly coated onto the patterned membrane (F-form (SO3 F)). The surface area of the patterned membranes was increased 2.12 times. The power density of the MEAs with the patterned membranes was also increased 24.2%.